Analysis of Regional Financial Constraints and Management - Simanjuntak, Eben Henry (LPPM Universitas Negeri Jakarta, 2024)
This research aims to identify the inhibiting factors affecting the sustainability of the innovation in the Electronic Financial Monitoring Information System (SiMOLEK) application at the Ministry of Home Affairs, particularly in the management of local finances and the evaluation process of accountability for the implementation of the Regional Budget. The study employs a qualitative descriptive approach, gathering data through observations and interviews with key informants who have authority, tasks, and functions related to the operation of SiMOLEK. The inhibiting factors analyzed are based on the results of studies conducted by Deloitte and KPMG, adjusted for relevance to the research object, including politics, lack of finance, leadership, technology, culture, and insufficient technical skills. The research findings indicate that the inhibiting factors causing the unsustainability of the SiMOLEK application innovation are politics, lack of finance, leadership, and technology.